Comparative analysis of student performance on the y-balance test - Tanasă Bogdan Ionuţ; Vizitiu Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
In the case of a physical education and sport teacher, the way in which he or she orients his or her mindset can contribute significantly to communicating and working effectively with students and can positively influence the outcomes of the educational process. The aim of this paper is to conduct a comparative analysis of students' performance on the Y-Balance test, evaluating and comparing their results to identify and understand differences and similarities in functional ability and balance. The objectives of the study: to identify and analyze student balance levels between the experimental group (who played weekly basketball) and the control group (who followed the regular school curriculum); to analyze differences in performance on the Y Balance test between the two groups of students to determine if playing weekly basketball had a significant impact on balance compared to the control group; To differentiate the results of the Y Balance test in the group that practiced basketball during the experimental period (September - December 2023) and the control group that followed the standard school curriculum, in order to highlight possible changes in balance; To analyze and interpret the balance results obtained, providing an understanding of how regular basketball practice can influence students' balance.